The Influence of Asset Growth, Asset Structure and Profitability on Company Value in Industrial Companies on The IDX - Melani Octavia; Adila Sari; Natasha Natasha; Seprint Purva; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This study uses associative tests to analyze and obtain empirical evidence, whether asset growth, asset structure and profitability have a significant effect on the company's value. The data used is secondary data taken from the official website, namely www.idx.go.id. The results of this study showed that individually asset growth had a positive and significant effect on the company's value, then individually asset structure and profitability had a positive and insignificant effect on the company's value. However, simultaneously the three independent variables have a significant effect on the value of the company with an influence value of 15%, where the other 85% value is influenced by other variables that are not included by the researcher.